1969
DOI: 10.1021/j100724a011
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance study of radiation-induced centers of chemical activity in a silica-alumina gel

Abstract: The esr spectrum of a 7-irradiated silica-alumina gel has a line 44.5 ± 0.5 G wide at g = 2.0088 ± 0.0005 which is partially resolved into six components separated by 8.5 ± 0.2 G; superimposed on this broad line is a narrow line at g = 2.0010 ± 0.0005. The broad line is identified with a positive hole trapped at an aluminum atom present substitutionally in the silica matrix. The narrow, line is attributed to an electron trapped at one of several kinds of oxygen vacancies and seems to result from a reaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In the y-radiolysis studies EPR spectra of holes on silica-alumina gel surfaces were stated to be poorly resolved and resulted in a broad line. 35 A part of MV,+ species is stable for several months in the absence of O2. As soon as oxygen/air is introduced into the sample, the blue color, and the corresponding spectral absorption The reaction of photogenerated MV,+ with O2 on a silica gel surface has been studied in both steady-state and timeresolved mode, where the formation of superoxide anion (O2"-)…”
Section: Methodsmentioning
confidence: 98%
“…In the y-radiolysis studies EPR spectra of holes on silica-alumina gel surfaces were stated to be poorly resolved and resulted in a broad line. 35 A part of MV,+ species is stable for several months in the absence of O2. As soon as oxygen/air is introduced into the sample, the blue color, and the corresponding spectral absorption The reaction of photogenerated MV,+ with O2 on a silica gel surface has been studied in both steady-state and timeresolved mode, where the formation of superoxide anion (O2"-)…”
Section: Methodsmentioning
confidence: 98%
“…In fact, in silicaÈalumina gel a similar signal was interpreted as a positive hole trapped on a bridging oxygen atom that is bonded to an aluminium present substitutionally in the silica matrix. 18 The isotropic pentet Q with spin Hamiltonian parameters mT and represents a tetrameric silver A iso \ 13.9 g iso \ 1.973 cluster located inside an octagonal prism.11 Similar Ag 4 3s ignals were observed in AgCs-rho zeolite after H 2 reduction10 as well as in c-irradiated AgH-rho zeolite.11 The third and fourth lines of pentet Q show some additional features and their intensities are lower than one would expect from the binominal intensity ratio. We earlier proposed that these irregularities resulted from the overlapping of a low intensity quartet of the cluster which is the precursor of Ag 3 2t he silver tetramer.11…”
Section: Dehydrated Zeolite Rhomentioning
confidence: 99%
“…High surface area silica is one of the most widely used catalyst supports. As such, and along with alumina and zeolites, it has been of interest as a support for high-energy radiation studies. Extensive photochemical studies are also reported on oxide surfaces. The photoinduced reactions of free radicals, radical ions, and excited states have all been studied on these surfaces. From the view of kinetics the fractal, rigid, and heterogeneous nature of these surfaces necessitate a careful consideration of the detailed nature of the reactions on these surfaces.…”
Section: Introductionmentioning
confidence: 99%